Evaluation of early abdominopelvic computed tomography in patients with acute abdominal pain of unknown cause: prospective randomised study. Issue 7377 (14th December 2002) - Ng, Chaan S; Watson, Christopher J E; Palmer, Christopher R; See, Teik Choon; Beharry, Nigel A; Housden, Barbara A; Bradley, J Andrew; Dixon, Adrian K
Abstract: Objectives: To evaluate the impact of early abdominopelvic computed tomography in patients with acute abdominal pain of unknown cause on length of hospital stay and accuracy of diagnosis. Design: Randomised, prospective controlled trial. Setting: Teaching hospital in England. Participants: 120 patients admitted with acute abdominal pain for which no immediate surgical intervention or computed tomography was indicated. Intervention: 55 participants were prospectively randomised to early computed tomography (within 24 hours of admission) and 65 to standard practice (radiological investigations as indicated). Main outcome measures: Length of hospital stay, accuracy of diagnosis, and, owing to a possible effect on inpatient mortality, deaths during the study. Results: Early computed tomography reduced the length of hospital stay by 1.1 days (geometric mean 5.3 days (range 1 to 31) v 6.4 days (1 to 60)), but the difference was non-significant (95% confidence interval, 8% shorter stay to 56% longer stay, P=0.17). Early computed tomography missed significantly fewer serious diagnoses. Seven inpatients in the standard practice arm died. Only 50% (59 of 118) of diagnoses on admission were correct at follow up at 6 months, but this improved to 76% (90) of diagnoses after 24 hours. Conclusions: Early abdominopelvic computed tomography for acute abdominal pain may reduce mortality and length of hospital stay. It can also identify unforeseen conditions and potentially serious complications.